Successful Hemostasis With Prolonged Balloon Inflation at the Proximal Site of the Coronary Perforation - Xiaolong Zheng; Yunxiang Wang; Yaosheng Mei; Changchun Lai; Yiqun Wang (Clinical Medicine Insights: Case Reports, 2023)
Coronary perforation (CP) is a rare complication of percutaneous coronary intervention (PCI) and can lead to pericardial tamponade. Prolonged balloon inflation is a reasonable treatment for CP, but there is no standard recommendation on the preferable choice between the balloon site for prolonged balloon inflation (ie, proximal and in situ of the perforation). We present a rare case of successful prolonged balloon inflation at the proximal site of the CP after the failure of balloon inflation at the site of perforation. The patient developed CP during balloon inflation post-stent, rapidly progressing to cardiac tamponade. In situ prolonged balloon inflation (3 times) failed to close the CP, but proximal inflation could manage the CP. The take-home message from this case is that balloon expansion at the proximal site could be better than in situ of perforation in patients with CP after PCI.